Manajemen Berbasis Sekolah dalam Meningkatkan Kualitas Belajar Siswa - Anam Khoirul Moh Khoirul Anam (Jawda: Journal of Islamic Education Management, 2022)
School-Based Management (SBM) is an alternative form of school or madrasa management, in the education decentralization program, where schools have the right to adapt better and more adequate education to their students. SBM is a strategy in managing education in madrasas that optimizes every madrasa's internal resources. The type of research is qualitative research, with data collection techniques through interviews, observation, and documentation. In the analysis using several stages, namely; data reduction, data presentation, drawing conclusions and verification. The results of the research show that the planning and implementation of activities carried out are following standard procedures given by the head of the madrasa by applying indicators to improve the quality of student learning.